Personality Analysis of The Main Characters in Tere Liye's Novel Pulang, Through Literature Psychology Approach - Yulita, Maria Yelinda (Lembaga Riset Mutiara Akbar, 2022)
Analysis of the Main Character's Personality in Tere Liye's Pulang Novel Through a Literary Psychology Approach. Maumere: Faculty of Social Sciences and Humanities Education, IKIP Muhammadiyah Maumere, 2021. This thesis discusses the personality psychology of the main character in the novel Pulang Karya Tere Liye through a literary psychology approach. The psychology of the main character's personality in the novel Pulang is interesting to discuss because Bujang's personality tells the story of his journey home through various obstacles, fighting in wars and facing betrayal by his own friends. The purpose of this study is to describe the personality of the main character in the novel Pulang Karya Tere Liye. This type of research is descriptive qualitative, using content with data sources from the novel Pulang by Tere Liye. The analysis technique, with the technique of reading repeatedly, notes the important parts and describes the personality of the main character so that the personality of the main character that will be studied can be known. The results of this study include: first, the results of research on the psychology of the main character's personality in the novel Pulang by Tere Liye examines the personality of the main character Bujang by using personality structures such as Id, Ego and Superego. The two Id structures contained in the personality of the main character Bujang (The Wild Boar) in the Novel Pulang by Tere Liye are impatient, grouchy, while the Ego contained in the personality of the main character Bujang is Bujang's attitude who is a stubborn figure, impatient and selfish, and the Superego contained in the Bujang character is a genius attitude inherited from his parents. From the results of this study, it can be concluded that the psychology of the personality of the main character in the novel Pulang by Tere Liye is contained in the structure of the id, ego and superego